ACTIVE-DIRECTIVE STRATEGY IN THE IMPROVEMENT OF NIGERIAN ADULT-LEARNERS’ TEACHING PERCEPTION AND EFFECTIVENESS (1991)
This study investigated the relative effectiveness of active-directive learning strategy over lecture method in enhancing the satisfaction, self-concept and cognitive performance of adult learners. One hundred adults; holders of Teachers’ Grade Two Certificate with a minimum of five years experience were selected by cluster sampling. The age-range was between twenty-eight and fifty years. Using a 2x 2 factorial design, fifty adult learners were exposed to the experimental Programme while fifty others served as the control. Three psychological instruments namely - Akinboye Self-Concept Scale with a coefficient alpha of =0.75, Adult Learner Perception of Programme Scale (&=0.98) and Teaching Effectiveness Scale (&=0.89) were validated and used as criterion measures. They were administered before and after treatment. Nine hypotheses were tested at 0.001 level of significance. The following results were obtained: (i) Treated subjects showed no main significant increase in self-concept compared with untreated subjects. (F = 0.71; df = 1/98, NS). (ii) Results from t-test analysis indicated that the experimental subjects improved significantly on self-concept. There was a significant increase in the self- concept of high self-concept active-directive group compared with the high self-concept control group. (t = 9.62, p < . 001, df = 47) The high self-concept active-directive strategy was superior to the low self- concept control (t = 14.53, p. < 001, df = 49). Treated subjects showed significant increase in satisfaction as measured by the perception of programme scale. (F = 9.48, df = 1/96, p < 001), (t = 87.92, df = 47, p < . 001), (t = 86.19, df=49, p< .001), (t = 77.99, df= 49, p < .001). There was a significant increase in the cognitive performance of treated subjects (F = 17.64, df = 1/96, p < 001). Active-directive was significantly superior to the control. (t = 19.63; df= 47, p< .001), (t = 12.02, df = 49, p < .001), (t = 11.04, df=49, p< .001). Active-directive Learning Strategy proved to be effective in enhancing the cognitive attainment and satisfaction of learners. The relevant implications in the instruction and training of adult learners were discussed. Recommendations were also made for adult educators who are concerned with skill-building effectiveness and for extension workers.